Art:21 art in the twenty-first century. Season five production of Art21 Inc. (Art21, Inc. ; distributed by PBS Home Video, 2009)
Through in-depth profiles and dynamics behind-the-scenes footage featuring artists speaking directly about their inspirations and ideas, Season Five shows a broad range of artistic practice, technical innovation, projects in hangar-like studios to those working in the quiet of more intimate studio settings.